Catalyst, catalytic system containing catalyst as well as preparation method and application of catalyst

By using high-strength, high elasticity and lightweight suspension catalysts, the problems of low efficiency, difficulty in recycling and waste of materials in actual applications are solved, and efficient water treatment effect is achieved.

CN119702083APending Publication Date: 2025-03-28NANJING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311265322.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In actual applications, existing granular and powdered catalysts have problems such as low catalytic efficiency, difficult recycling, and serious material waste, resulting in unsatisfactory use.

Method used

A catalyst with high strength, high elasticity and light weight suspension characteristics is provided, including an elastic matrix and a catalytically active metal component. The matrix is ​​vulcanized and a channel through thickness is opened on the surface to improve the water-water properties and mass transfer efficiency of the catalyst.

Benefits of technology

This catalyst can effectively improve catalytic efficiency, reduce recovery costs, reduce material waste, and exhibit good suspension and mass transfer properties in water treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119702083A_ABST
    Figure CN119702083A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst as well as a preparation method and application thereof. The catalyst comprises a matrix and a component I positioned on the matrix, the base body comprises a polyurethane elastomer; the component I has catalytic activity and comprises one or more metals, and the metals comprise any one or two or more of iron, cobalt, nickel, copper, zinc and titanium; the amount of the metal accounts for 15-25 wt% of the total amount of the catalyst according to the weight percentage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sewage treatment, and in particular relates to a catalyst, a catalytic system containing the catalyst, and a preparation method and application thereof. Background Art

[0002] As one of the physicochemical treatment technologies, advanced oxidation treatment technology has the advantages of high treatment efficiency and more thorough destruction of toxic pollutants, and is widely used in the pretreatment process of toxic and difficult-to-degrade industrial wastewater. It has gradually become a hot spot in water treatment technology research. The current advanced oxidation technologies mainly include chemical oxidation, electrochemical oxidation, wet oxidation, supercritical water oxidation and photocatalytic oxidation. Taking chemical oxidation technology as an example, the chemical oxidation technology includes Fenton oxidation, Fenton-like oxidation, ozone oxidation, etc., which generally uses chemical oxidants to treat organic wastewater under the action of catalysts, and generates active free radicals with high oxidizing properties (·OH, ·O2 - , ·O, etc.) to remove refractory organic matter to improve the biodegradability of wastewater, or directly oxidize and degrade organic matter in wastewater to stabilize it. This type of technology usually has the advantages of rapid reaction, simple process, strong oxidation ability and easy reaction conditions. It is a high-efficiency and low-consumption sewage treatment technology with good development prospects in the field of sewage treatment. However, the existing chemical oxidation technology has problems such as low catalytic efficiency and difficulty in catalyst recovery, and the treatment effect still has a lot of room for improvement.

[0003] Taking ozone oxidation as an example, the existing catalytic ozone oxidation catalysts are mainly three-dimensional granular catalysts or powdered catalysts. Granular catalysts have a high specific surface area and are usually used in ozone fixed bed processes in a filling manner, but they have the defects of particle deposition and waste of catalytic performance of materials inside the particles. The reason is that the main sites of active free radicals are oxygen vacancies, Lewis acids and functional groups on the catalyst surface, while existing granular catalysts are usually spherical materials with a particle size of 3-5mm. The large particle size makes its internal structure unable to directly participate in catalysis. The large amount of internal structure not only reduces the volume density of active sites, but also leads to material waste and increased costs.

[0004] Compared with granular catalysts, powdered catalysts are as small as micro / nano levels, which can obtain higher specific surface area and increase the contact probability with catalysts / organic matter to break through the mass transfer bottleneck in low-concentration wastewater treatment. However, powdered catalysts require additional membrane separation and recovery processes, which are costly and complex to operate, and are difficult to apply. Therefore, they have the defect of large catalyst loss, which will also cause serious material waste and increased costs.

[0005] Therefore, existing granular and powdered catalysts have application bottlenecks that are difficult to overcome in practical applications, resulting in unsatisfactory actual use effects. Summary of the invention

[0006] 1. Problem to be solved

[0007] In view of the problem that existing granular catalysts or powdered catalysts are not well used in practice, the present invention provides a catalyst and a catalytic system containing the catalyst, which has the characteristics of high strength, high elasticity, light suspension, and low difficulty in separation and recovery;

[0008] At the same time, a method for preparing the catalyst is provided;

[0009] Furthermore, the provided catalyst or catalyst system is applied to water treatment.

[0010] 2. Technical solution

[0011] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0012] According to the purpose of the present invention, the catalyst provided in the first aspect of the present invention comprises:

[0013] A substrate, and a component I located on the substrate;

[0014] The matrix has elastomeric characteristics, and the matrix includes one or more elastomers;

[0015] The component I has catalytic activity, and the metal component I includes one or more metals, and the metal includes any one or two or more of iron, cobalt, nickel, copper, zinc, and titanium;

[0016] Calculated by weight percentage, the amount of the metal accounts for 15-25wt% of the total amount of the catalyst, preferably the amount of the metal accounts for 15.7-24.2wt% of the total amount of the catalyst; more preferably, the amount of the metal accounts for 16-24wt% of the total amount of the catalyst;

[0017] It should be noted that for catalysts, the flexibility of the matrix is ​​very important during use, such as when it is used in water treatment catalysis. During use, the integrity of the material can be well preserved, ensuring that the catalyst has good mechanical properties and structural stability, avoiding the powdering of the catalyst, and making separation and recovery more convenient; without being limited by theory, the material with a certain flexibility will have better toughness and lower brittleness, and the probability of breakage during use will be lower. For example, the most typical traditional porous anodized transition metal template has a regular array of holes on its surface, and the material is extremely brittle. If a catalyst is prepared using this as a matrix, it will be fragile during use and suffer great losses.

[0018] The catalyst provided by the present invention has a matrix with elastomeric characteristics, so that the matrix has high plasticity, corrosion resistance, high strength and high elasticity. Based on this, on the one hand, the problem of easy corrosion of traditional metal-based catalysts can be effectively avoided, and the service life and recovery rate of the catalyst can be effectively improved, while also reducing secondary pollution caused by metal loss; on the other hand, when it is used for catalytic oxidation for water treatment, the catalyst can be placed in a deformation state of stretching, and / or compression, and / or torsion, so as to achieve the purpose of utilizing the elastic potential energy generated by the deformation to enhance the catalytic effect.

[0019] According to any embodiment of the first aspect of the present invention, the elastomer includes any one or two or more of polyurethane elastomer, styrene block thermoplastic elastomer, polyester elastomer and polyolefin elastomer; preferably includes polyurethane elastomer.

[0020] According to any embodiment of the first aspect of the present invention, the substrate comprises a polyurethane elastomer.

[0021] According to any embodiment of the first aspect of the present invention, the matrix is ​​composed of the polyurethane.

[0022] According to any embodiment of the first aspect of the present invention, the metal comprises a metal sulfide that has been sulfided; or

[0023] The elastomer comprises a vulcanized elastomer; or,

[0024] The metal comprises a metal sulfide that has been vulcanized, and the elastomer comprises an elastomer that has been vulcanized; or

[0025] The elastomer includes an elastomer that has been vulcanized, and the metal combines with sulfur in the elastomer to form a metal sulfide.

[0026] According to any embodiment of the first aspect of the present invention, the substrate is a vulcanized polyurethane elastomer.

[0027] According to any embodiment of the first aspect of the present invention, the substrate is a layered substrate having a channel extending through the thickness of the layered substrate.

[0028] Compared with the traditional "whole sheet" two-dimensional catalyst, the matrix of the catalyst of the present invention can improve the water permeability of the catalyst by opening a through channel, reducing the water permeability resistance of the sheet structure of the two-dimensional catalyst. When the catalyst is impacted by water, the layered catalyst with water permeation holes can be more evenly suspended in the water, further improving the mass transfer efficiency of the catalyst.

[0029] According to any embodiment of the first aspect of the present invention, the thickness H1 of the layered substrate is 200 to 800 μm; preferably, the thickness H1 is 400 to 800 μm; and more preferably, the thickness H1 is 600 to 800 μm.

[0030] It should be noted here that, in fact, the thickness of the catalyst provided by the present invention depends to a large extent on the thickness of the substrate. The catalyst provided by the present invention adopts a thin layered substrate, such as a polyurethane elastomer sheet. On the one hand, this type of substrate can neutralize the defects of granular or powdered catalysts that are difficult to recover and separate; on the other hand, the thinner the substrate, the more it can eliminate the ineffective structure inside the catalyst to adapt to the surface reaction of catalyzing ozone. However, it should be noted that if the substrate is too thin, it will affect the use strength of the final catalyst.

[0031] According to any embodiment of the first aspect of the present invention, the catalyst further comprises component II located on the substrate; the component II is an adsorptive powder; and the particle size of the powder is 40 to 60 μm.

[0032] According to any embodiment of the first aspect of the present invention, the surface of the substrate has pores formed after the pore-forming agent is dissolved.

[0033] It should be noted that after the pores are formed on the substrate surface, the roughness of the substrate surface can be increased and a microporous structure can be created for the substrate surface. At the same time, the adsorbent powder component II attached to the substrate surface also increases the roughness of the substrate surface, further improving the catalyst's ability to adsorb water. At the same time, it is also beneficial for the catalyst to be suspended in water after the reactor is aerated during its application in the wastewater to be treated.

[0034] According to the purpose of the present invention, the second aspect of the present invention provides a catalytic system containing a catalyst, the catalytic system comprising the catalyst provided by any embodiment of the first aspect of the present invention, and a system component that causes the catalyst to deform;

[0035] The component is preferably a porous shell or a porous membrane.

[0036] According to the purpose of the present invention, the third aspect of the present invention provides a method for preparing the catalyst, the method comprising the following steps:

[0037] The following steps are involved:

[0038] (A) preparing a liquid matrix or a raw material liquid for synthesizing a matrix;

[0039] Prepare the mold;

[0040] preparing a powder raw material, wherein the powder raw material includes a metal component;

[0041] (B) laying the powder raw material on the surface of the mold;

[0042] (C) injecting the liquid matrix or raw material liquid into a mold;

[0043] Spreading powdered raw materials on the surface of the liquid matrix or raw material liquid in the mold;

[0044] (D) curing treatment;

[0045] (E) The product obtained by the curing treatment is subjected to a vulcanization treatment using a vulcanizing composition.

[0046] The present invention adopts a one-step injection molding method to prepare the catalyst, which is different from the traditional method of first preparing the matrix material and then loading the active components on the matrix material. The method is convenient and simple to operate and is suitable for large-scale mass production.

[0047] According to any embodiment of the third aspect of the present invention, the powdered raw material further comprises a component having adsorptive properties.

[0048] According to any embodiment of the third aspect of the present invention, the powder raw material further comprises a component having pore-forming ability (pore-forming agent), and preferably the component is water-soluble.

[0049] According to any embodiment of the third aspect of the present invention, the method further comprises step (F): performing a decomposition treatment of the pore-forming agent.

[0050] According to any embodiment of the third aspect of the present invention, the matrix includes any one or two or more of a polyurethane elastomer, a styrene block thermoplastic elastomer, a polyester elastomer and a polyolefin elastomer.

[0051] According to any embodiment of the third aspect of the present invention, a plurality of protrusions are provided at the bottom of the mold; the protrusions are used to form channels penetrating the thickness of the catalyst in the thickness direction.

[0052] It should be noted that by controlling the shape, size, distribution density, etc. of the protrusions at the bottom of the mold, the layered catalyst can leave a water-passing "channel" for the intended purpose after solidification.

[0053] According to any embodiment of the third aspect of the present invention, the metal component is selected from any one or two or more of iron, cobalt, nickel, copper, zinc and titanium, and the amount of the metal component on the mold surface is 0.0050-0.0080 g / cm 2 The preferred laying amount is 0.0056 to 0.0084 g / cm 2; It is further preferred that the laying amount is 0.006 to 0.008 g / cm 2 .

[0054] According to any embodiment of the third aspect of the present invention, the component with adsorption performance includes any one or two or more of activated carbon, graphene, zeolite molecular sieve, activated alumina, and diatomaceous earth; and the amount of the component on the mold surface is 0.002 to 0.006 g / cm 2 Preferably, the laying amount is 0.0025 to 0.0052 g / cm 2 ; It is further preferred that the laying amount is 0.003 to 0.005 g / cm 2 .

[0055] According to any embodiment of the third aspect of the present invention, the component with pore-forming ability includes but is not limited to one or more of NaCl, Na2CO3, NaNO3, Na2SO4, KCl, K2CO3, K2SO4, KNO3, MgCl2, Mg(NO3)2, MgSO4, ZnCl2, CuCl2, CuSO4, CaCl2, pentaerythritol, glucose, sucrose, and lactose, and the amount of the component on the mold surface is 0.004 to 0.009 g / cm 2 ; It is further preferred that the laying amount is 0.006 to 0.008 g / cm 2 .

[0056] According to any embodiment of the third aspect of the present invention, the vulcanization treatment in step (E) includes low temperature vulcanization and high temperature vulcanization;

[0057] The temperature of the low-temperature vulcanization is no more than 90°C, and the vulcanization time is 5 to 10 minutes; preferably 70 to 80°C;

[0058] The high temperature vulcanization temperature is not less than 120°C, and the vulcanization time is 5 to 10 minutes; preferably 130 to 150°C.

[0059] The vulcanization composition comprises a vulcanizing agent, a vulcanization accelerator and a reinforcing agent, and the mass ratio of the three to the elastomer is (5-10): (3-5): (40-50): (70-90).

[0060] Based on the catalyst provided in the first aspect of the present invention, and / or the catalytic system containing the catalyst provided in the second aspect, and / or the catalyst prepared by the method in the third aspect, the fourth aspect of the present invention provides the use of the catalyst or the catalyst system in catalytic oxidation for water treatment.

[0061] According to any embodiment of the fourth aspect of the present invention, during the application of the catalyst in water treatment by catalytic oxidation, the catalyst is placed in a deformation state of tension, and / or compression, and / or torsion.

[0062] 3. Further explanation on the technical solution

[0063] Any embodiment of any aspect of the present invention can be combined with other embodiments without contradiction. In addition, in any embodiment of any aspect of the present invention, any technical feature can be applied to the technical feature in other embodiments without contradiction.

[0064] Under the premise that there is no contradiction, any technical feature of any aspect of the present invention or any embodiment of any aspect is also applicable to any other embodiment or any embodiment of any other aspect. Of course, when applicable to each other, the corresponding features can be appropriately modified if necessary. The various aspects and features of the present invention are further described below.

[0065] All documents cited in the present invention are incorporated herein by reference in their entirety, and if the meanings expressed in these documents are inconsistent with the present invention, the description of the present invention shall prevail. In addition, the various terms and phrases used in the present invention have the general meanings known to those skilled in the art. Even so, the present invention still hopes to provide a more detailed description and explanation of these terms and phrases. If the terms and phrases mentioned are inconsistent with the known meanings, the meanings expressed in the present invention shall prevail.

[0066] Unless otherwise indicated, it should be understood that each individual element in a list and each combination of individual elements in the list will be interpreted as a different embodiment. For example, a list of embodiments represented as "A, B, or C" should be interpreted to include embodiments "A", "B", "C", "A or B", "A or C", "B or C", or "A, B, or C".

[0067] In the present disclosure, the singular forms of the articles "a," "an," and "the" also include the corresponding plural references, and a reference to a specific value includes at least that specific value unless the context clearly indicates otherwise. Thus, for example, a reference to "a substance" is a reference to at least one of that substance and equivalents thereof.

[0068] The terms including ordinal numbers such as "first" and "second" can be used to explain various components or fluids, but these components and fluids are not limited by these terms. Therefore, without departing from the teachings of the present disclosure, these terms are only used to distinguish the component / fluid from another component / fluid.

[0069] When items are described by using the conjunction terms "... and / or...," etc., the description should be understood to include any one of the associated listed items and all combinations of one or more thereof.

[0070] In general, the use of the term "about" indicates an approximate value that may vary depending on the desired properties obtained by the disclosed subject matter, and will be interpreted in a context-dependent manner based on function. Therefore, one of ordinary skill in the art will be able to interpret a certain degree of difference on a case-by-case basis. In some cases, the number of significant figures used when expressing a particular value can be a representative technique for determining the difference allowed by the term "about". In other cases, a gradient in a range of values ​​can be used to determine the range of differences allowed by the term "about". Further, all ranges in this disclosure are inclusive and combinable, and reference to the values ​​stated in the range includes each value within the range.

[0071] In the present invention, the term "comprising" or "containing" means that various components can be used together in the composition of the present invention. Therefore, the terms "consisting mainly of" and "consisting of" are included in the terms "comprising" or "containing".

[0072] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs; the terms used herein and / or include any and all combinations of one or more of the associated listed items.

[0073] In order to demonstrate the technical solutions and advantages of the present invention, the technical solutions in the embodiments of the present invention will be fully described below.

[0074] The catalyst provided in the first aspect of the present invention comprises a substrate and a component I located on the substrate.

[0075] In the context of the present invention, the "matrix" is required to be able to produce a certain degree of deformation and internal force under a certain external force. From the perspective of catalyst recovery and reuse, it is preferred that the "matrix" has the same or similar characteristics as the elastomer, that is, a material that can return to its original shape after the external force is removed.

[0076] Based on the above, in order to make the "matrix" meet the above requirement of "having the same or similar characteristics as the elastomer", an elastomer (preferably a thermoplastic elastomer) can be added to the matrix, and the amount of the elastomer added is not less than 95% by weight; preferably, the amount added is as close to 100% as possible, that is, excluding the unavoidable interference of impurities, the amount added is 100%.

[0077] In the context of the present invention, the "elastomer" includes thermosetting elastomers and thermoplastic elastomers. Common thermosetting elastomers include, for example, styrene-butadiene rubber, butadiene rubber, isoprene rubber, ethylene-propylene rubber, butyl rubber, chloroprene rubber and nitrile rubber, etc.; common thermoplastic elastomers include, for example, polyurethane elastomers, styrene block thermoplastic elastomers, polyester elastomers and polyolefin elastomers.

[0078] In the present invention, a thermoplastic elastomer is preferably added to the matrix, and the thermoplastic elastomer is vulcanized.

[0079] In the context of the present invention, as the "component I", one of its main functions is "catalytic" performance; the "catalytic" performance, for example, can be catalytic ozone oxidation to produce hydroxyl radicals, or catalytic hydrogen peroxide to produce hydroxyl radicals; as the "matrix", its thickness H1 can be considered from the aspects of ensuring the lightness of the catalyst and reducing the vulnerability of the catalyst. Generally, too small a thickness increases the vulnerability of the catalyst, and too large a thickness affects the lightness of the catalyst, resulting in the catalyst failing to achieve the lightness due to the excessive thickness of the matrix layer, which is not conducive to suspension; based on this, it is recommended that the H1 can be arbitrarily selected within the range of 200 to 800 μm; for example, H1 can be 200 μm, 250 μm, 300 μm, 350 μm, 400 μm, 450 μm, 500 μm, 550 μm, 600 μm, 650 μm, 700 μm, 750 μm, 800 μm.

[0080] Based on the requirement of the “catalytic” performance, the “component I” comprises at least one metal selected from iron, cobalt, nickel, copper, zinc or titanium.

[0081] In addition, considering the effect on the catalytic activity, calculated by weight, the amount of the metal from iron, cobalt, nickel, copper, zinc or titanium accounts for at least 15-25wt% of the total amount of the catalyst; for example, calculated by weight, the amount of the metal from iron, cobalt, nickel, copper, zinc or titanium accounts for 15-23wt%, 15-20wt%, 15-18wt%, 16-23wt%, 16-20wt%, 16-18wt%, 17-23wt%, 17-20wt%, 17-18wt%, 18-23wt%, 18-20wt%, 19-23wt%, 19-20wt% of the total amount of the catalyst.

[0082] As the "metal", it is added in the form of powder particles. Regarding the particle size D of the powder "particles", it is recommended that its size is not less than the thickness H1 of the "matrix". The reason is that it is hoped to ensure that the powder "particles" can be as much as possible "exposed" on the surface of the layered "matrix" as possible, so that the catalyst has more catalytic active sites. Based on this, for example, when the thickness H1 of the "matrix" is selected from a specific value in the range of 200 to 800 μm, the particle size D of the "powder" at least meets the condition: 200 microns ≤ D < 900 microns, and, at the same time, H1 ≤ D needs to be satisfied. In addition, as the "metal", it is the same as the "matrix", and both are subjected to sulfurization treatment, and finally the "metal from iron, cobalt, nickel, copper, zinc or titanium" in the catalyst provided by the present invention is converted into sulfided metal.

[0083] As the "component I", the individual particles of the powder contained therein are present in the layered "matrix" in an embedded manner.

[0084] Based on the requirement of the "adsorption" performance, as the "component II", it contains at least one adsorptive material, for example, any one or two or more of activated carbon, graphene, and zeolite molecular sieves. The adsorptive material is mainly distributed on the surface of the layered "matrix" of the "catalyst". Based on this, the adsorptive material is required to be in powder form, and the "powder" can, for example, pass through a sieve of not less than 200 meshes.

[0085] In addition, in order to improve the suspension and separation capabilities of the catalyst during its application, the catalyst is required to be a two-dimensional (layered) catalyst, so the catalyst provided by the present invention has a layered matrix. On this basis, in order to further reduce the water resistance of the two-dimensional catalyst, the present invention has made further improvements to the two-dimensional metal catalyst, that is, holes that penetrate the thickness layer of the catalyst are provided on the layered matrix of the catalyst for water to pass through, also known as water "channels", and holes are formed on the surface of the layered matrix of the catalyst after the pore-forming agent is dissolved.

[0086] The setting of "pores formed after the pore-forming agent is dissolved" on the surface of the layered matrix of the catalyst can improve the roughness of the catalyst surface and enhance the catalyst's ability to suspend in liquid. The setting of the "channel" on the catalyst will enable the two-dimensional catalyst provided by the present invention to have good water permeability compared to traditional two-dimensional catalysts, reduce the water permeability resistance of the layered structure, and reduce the impact load on the catalyst when the catalyst is impacted by water inflow, ensuring that the "two-dimensional catalyst" with a layered structure can be more evenly suspended in water under the impact of water inflow and aeration, further improving the mass transfer efficiency of the catalyst.

[0087] As the "channels" mentioned above, their density and size should be appropriately set to ensure that the layered structure has sufficient effective catalytic area to achieve efficient catalytic ozone oxidation. Specifically:

[0088] The size of the "channel" can be determined, for example, based on the specific area of ​​the "layered matrix". Taking the "layered matrix" of the unit area as an example, the unit area is divided into six equal parts, and the shape of the "through-going channel" is the same as that of each of the equal parts, and the area is one-fourth of each of the equal parts.

[0089] The arrangement density of the "channels" per unit area of ​​the "layered matrix" can be specifically described as: dividing the unit area into six equal parts, and making a "through channel" with the center point of each part as the reference;

[0090] The second aspect of the present invention provides a method for preparing the catalyst; comprising steps (A) to (E), (F); preferably further comprising step (F) after step (E).

[0091] Regarding A1 in the step (A): preparing a liquid matrix or a raw material liquid for synthesizing a matrix, wherein the matrix includes an elastomer;

[0092] As mentioned above, in order to make the "matrix" meet the requirement of "having the same or similar characteristics as the elastomer", an elastomer (preferably a thermoplastic elastomer) can be added to the matrix, and the amount of the elastomer added is not less than 95% by weight; the preferred amount is as close to 100% as possible, and the most ideal amount is 100%.

[0093] The "elastomer" is preferably a thermoplastic elastomer. Common thermoplastic elastomers include, for example, polyurethane elastomers, styrene block thermoplastic elastomers, polyester elastomers, and polyolefin elastomers.

[0094] For example, if the "elastomer" is a polyurethane elastomer, the liquid matrix refers to the "polyurethane elastomer" softened / melted and converted into a liquid state by heating; and the raw materials used to synthesize the matrix refer to the raw materials for synthesizing the matrix calculated by weight, and the raw materials for synthesizing the matrix include:

[0095] (A) and (B) consist of:

[0096] (A) A polyisocyanate prepolymer composition prepared by the following reactions (i) and (ii):

[0097] (i) 40-60 parts of a diisocyanate selected from the following (a) and (b):

[0098] (a) p-phenylene diisocyanate, and 2,6-toluene diisocyanate; and

[0099] (b) trans-1,4-cyclohexane diisocyanate, and trans, trans-4,4′-dicyclohexylmethyl diisocyanate;

[0100] (ii) 90-100 parts of a polyol substantially free of any part that may oxidize at temperatures below 150° C., selected from the following (a), (b), and (c):

[0101] (a) polycarbonate polyol,

[0102] (b) polyester polyol, and

[0103] (c) a mixture of the polycarbonate polyol and the polyester polyol,

[0104] (B) 10-20 parts of a chain extender selected from the following materials which imparts thermal stability to the polyurethane elastomer:

[0105] (i) Aromatic symmetrical primary diamine chain extender:

[0106] (ii) a mixture of the aromatic primary diamine chain extender and the aromatic secondary diamine chain extender, and

[0107] (iii) a mixture of the aromatic primary diamine chain extender and the polyol;

[0108] Weigh 90-100 parts of polyol by weight, dehydrate at 130-140℃ for 1-2h under vacuum conditions, and cool to 80℃, mix with 40-60 parts of diisocyanate, and react at 120-130℃ for 50-60min to obtain a prepolymer. Then, preheat 10-20 parts of chain extender at 120℃, add to the prepolymer, stir, and react at 110-120℃ under vacuum conditions for 10-20min.

[0109] For example, if the "elastomer" is a polyester elastomer, the synthetic raw materials of the matrix include, by weight, xylitol and dibasic acid (dodecanedioic acid, itaconic acid, succinic acid, etc.), the molar ratio of xylitol to dibasic acid is 1:1; and it is synthesized by any known method.

[0110] For example, if the "elastomer" is a polyolefin elastomer, the synthetic raw materials of the matrix include, by weight: 50-70 parts of powdered styrene-butadiene rubber, 30-50 parts of polyethylene, 30-40 parts of filler (calcium carbonate), 4-8 parts of plasticizer (naphthenic oil), 0.8-1 parts of sulfur, 1-1.2 parts of accelerator M (2-mercaptobenzothiazole), 1-1.4 parts of accelerator DM (2, 2'-dithiobenzothiazole), 3-5 parts of zinc oxide, and 1010 parts of antioxidant. 1010) 1-3 parts, low molecular wax 0.8-1.2 parts; and synthesized by any known method.

[0111] As mentioned above, the “base” is preferably mainly composed of the “polyurethane elastomer” as described above.

[0112] Regarding step (A) A2: preparing a mold;

[0113] The focus of the "mold" used for catalyst curing and shaping is the design of the bottom. A number of protrusions are provided at the bottom of the mold. The height, shape and size of the protrusions are set according to the specific requirements of the water-passing "channel" to be present on the desired catalyst and the thickness of the catalyst (or its matrix), so as to form a water-passing "channel" that runs through the thickness of the catalyst in the thickness direction.

[0114] Regarding A3 in the step (A): powdered raw material;

[0115] The powder raw material includes any one or two or more metal raw materials selected from iron, cobalt, nickel, copper, zinc, and titanium; as the "metal raw material", it is used in powder form. The particle size D of the powder must be greater than the preset thickness of the "matrix";

[0116] The powder raw material also includes a component with adsorption properties; there are no special requirements for the material selection of the "component with adsorption properties", and examples thereof include: any one or two or more of activated carbon, graphene, and zeolite molecular sieves; as for the form of the "adsorbent material", it is preferred to select powder particles processed into the required particle size, for example, the adsorbent material powder can pass through a sieve of not less than 200 mesh.

[0117] The powder raw material also includes a component with pore-forming ability. Regarding the material selection of the "component with pore-forming ability", it is preferred that the component is water-soluble, and examples thereof include: one or more of NaCl, Na2CO3, NaNO3, Na2SO4, KCl, K2CO3, K2SO4, KNO3, MgCl2, Mg(NO3)2, MgSO4, ZnCl2, CuCl2, CuSO4, CaCl2, pentaerythritol, glucose, sucrose, and lactose.

[0118] There is no clear order of precedence among A1, A2 and A3 in the step (A).

[0119] Regarding the step (B): dispersing the powder raw material in the mold;

[0120] At the bottom of the mold, a layer of relatively mixed powder raw material is spread in a relatively uniform form. There is no mandatory requirement for the thickness of the powder raw material at the bottom of the mold. For example, it can be calculated according to the amount of metal components and / or components with adsorption properties and / or components with pore-forming ability contained in the powder raw material (calculated based on the uniform state of each component) laid on the mold surface or the amount of loading on the catalyst surface:

[0121] For example, the amount of the metal component laid on the mold surface is 0.0050 to 0.0080 g / cm 2 ; and / or, the loading amount of the metal component on the substrate surface is 0.0050 to 0.0080 g / cm 2 .

[0122] For example, the amount of the component with adsorption performance laid on the mold surface is 0.002-0.006 g / cm 2 ; and / or, the loading amount of the component having adsorption properties on the substrate surface is 0.002 to 0.006 g / cm 2 .

[0123] For example, the amount of the component with pore-forming ability laid on the mold surface is 0.004 to 0.009 g / cm 2 ; and / or, the loading amount of the component having pore-forming ability on the substrate surface is 0.004 to 0.009 g / cm 2 .

[0124] However, it is worth noting that since subsequent steps are required after solidification, the loading amount x of the powder raw material (or the components included in the powder raw material) on the substrate surface is not necessarily completely equivalent to the amount y contained on the surface of the final catalyst; usually the amount y is lost relative to the amount x (the vulcanization process will strengthen the metal, and due to the final soaking process, it is believed that the main loss comes from the pore-forming agent. According to the mass percentage of the catalyst before soaking, the loss is approximately 14.4% to 17.9%).

[0125] Regarding the step (C): injecting the liquid matrix or raw material liquid into the mold;

[0126] Usually, the mold is preheated to 100-120° C., and then the "liquid matrix" or "raw material liquid" is injected into the mold. When the thickness of the "liquid matrix" or "raw material liquid" in the mold reaches a predetermined target, the injection is stopped.

[0127] Regarding the step (C): spreading powdered raw material on the surface of the liquid matrix or raw material liquid in the mold;

[0128] The amount required after the injection is stopped is the same as that in step (B).

[0129] Regarding the step (D): curing treatment;

[0130] There is no special requirement for the curing treatment method, and the curing can be carried out by using the existing elastomer method based on the actual situation of the type of elastomer contained in the matrix. For example, if the matrix contains polyurethane elastomer, the liquid raw material can be directly gelled, and then the mold is closed and the pressure is increased to obtain the initial thin sheet-like layered product.

[0131] Regarding the step (E): performing a vulcanization treatment on the product obtained by the curing treatment using a vulcanization composition;

[0132] Calculated by weight, the vulcanization composition usually includes 5-10 parts of vulcanizing agent, 3-5 parts of vulcanization accelerator, and 40-50 parts of reinforcing agent to treat 70-90 parts of elastomer.

[0133] The "vulcanization treatment" mentioned above includes low temperature vulcanization and high temperature vulcanization;

[0134] The temperature of the low-temperature vulcanization is no more than 90°C, and the vulcanization time is 5 to 10 minutes; preferably 70 to 80°C. In this stage, the metal components of the surface layer are vulcanized to form sulfide metal.

[0135] The high temperature vulcanization temperature is not less than 120° C., and the vulcanization time is 5 to 10 minutes; preferably 130 to 150° C.; in this stage, the elastomer contained in the matrix is ​​vulcanized.

[0136] Regarding the step (F): performing a decomposition treatment of the pore-forming agent;

[0137] The product after the sulfidation treatment is cooled and then soaked in water to dissolve the water-soluble pore-forming agent on the surface, increase the roughness of the substrate layer / catalyst surface, and then dried to obtain the finished catalyst.

[0138] The present invention also provides a catalytic system containing a catalyst, wherein the catalytic system comprises the catalyst described in any one of the first aspects above or the catalyst prepared in any one of the second aspects above, and a system component that causes the catalyst to deform;

[0139] The component is preferably a porous shell or a porous membrane. One specific form of the porous shell is as follows Figure 3 Based on this, one of the specific forms of the catalytic system is as follows Figure 4-1 , Figure 4-2 As shown; the final object can be referenced Fig.13 or Figure 14-1 , Figure 14-2 shown.

[0140] However, it should be noted that the filling amount of the catalyst in the system components can be adjusted.

[0141] The present invention also provides a method for using the catalyst, which is applied to catalytic oxidation for water treatment;

[0142] During the application process, the catalyst is placed in a tensile, and / or compressive, and / or torsion deformation state.

[0143] Instruction Manual

[0144] Figure 1 This is a structural diagram of a mold for preparing a catalyst according to Example 1 of the present invention;

[0145] Figure 2 This is a schematic diagram of the catalyst structure of Example 1 of the present invention;

[0146] Figure 3 A schematic diagram of the structure of the system components for producing deformation of the catalyst;

[0147] Figure 4-1 A schematic diagram of a catalytic system containing the catalyst provided by the present invention;

[0148] Figure 4-2 A schematic diagram of a catalytic system containing the catalyst provided by the present invention;

[0149] Figure 5 This is a schematic diagram of an ozone catalytic oxidation operation device;

[0150] Figure 6 The catalytic effect diagram of Example 2 and Comparative Example 1 of the present invention;

[0151] Figure 7 The catalytic effect diagram of Example 2 and Comparative Example 2 of the present invention;

[0152] Figure 8 The quality graph of the catalyst prepared in Example 1 of the present invention after 5 recyclings;

[0153] Fig. 9 This is a scanning electron microscope image of metal particles embedded on the surface of the catalyst prepared in Example 1 of the present invention;

[0154] Fig.10 This is an EDS image of the catalyst surface prepared in Example 1 of the present invention;

[0155] Fig.11 This is an EDS image of the catalyst surface prepared in Example 1 of the present invention;

[0156] Fig.12 This is an EDS image of the catalyst surface prepared in Example 1 of the present invention;

[0157] Fig.13 A physical example diagram of a catalyst-containing catalytic system prepared in Example 1 of the present invention;

[0158] Figure 14-1 A physical diagram of a catalytic system containing the catalyst provided by the present invention;

[0159] Figure 14-2 A physical diagram of a catalytic system containing the catalyst provided by the present invention (corresponding to Figure 14-1 different angles of the image);

[0160] In the figure: 100, convex point of the mold; 200, catalyst (with a channel for passing water); 210, channel; DETAILED DESCRIPTION

[0161] The present disclosure may be more easily understood by reference to the following description in conjunction with the accompanying drawings and examples, all of which constitute a part of the present disclosure. It should be understood that the present disclosure is not limited to the specific products, methods, conditions or parameters described and / or shown herein. Further, the terms used herein are only used for the purpose of describing specific embodiments by way of example and are not intended to be limiting unless otherwise stated.

[0162] It should also be understood that, for the sake of clarity, certain features of the present disclosure may be described herein in the context of separate embodiments, but may also be provided in combination with each other in a single embodiment. That is, unless clearly incompatible or specifically not included, each separate embodiment is considered to be combinable with any other embodiment, and the combination is considered to represent another different embodiment. Conversely, for the sake of simplicity, the various features of the present disclosure described in the context of a single embodiment may also be provided individually or in any sub-combination. Finally, although a particular embodiment may be described as part of a series of steps or part of a more general structure, each step or substructure itself may also be considered to be an independent embodiment.

[0163] Example 1

[0164] 1-1) Catalyst - Polyurethane Elastomer Sheet:

[0165] This embodiment provides a catalyst, the catalyst comprising a substrate with a thickness H1 of 700 μm, and components I and II on the substrate which are adsorbent powders;

[0166] The substrate is made of polyurethane elastomer, and has pores on its upper and lower surfaces formed by the dissolution of the pore-forming agent. The substrate also has channels that penetrate its thickness.

[0167] The component I is cobalt metal (including metal sulfide / metal oxide); calculated by weight percentage, the amount of the metal accounts for 20wt% of the total amount of the catalyst; the elastomer includes a vulcanized elastomer, and the metal combines with sulfur in the elastomer to form a metal sulfide.

[0168] The component II is an activated carbon powder with a particle size of 40 to 60 μm.

[0169] 2-1) Catalyst system (hereinafter also referred to as catalytic capsule):

[0170] A 20 cm × 10 cm long and wide polyurethane elastomer sheet is cut into small sheets. The sheet size in this embodiment is 6.5 cm × 0.7 cm in length and width. Then, it is stuffed into each collected square plastic cage (3 cm × 3 cm × 3 cm in length, width and height) with water holes on the surface to make a single catalytic capsule, which can be stuffed into the external plastic cage in an arched shape.

[0171] 1-2) Catalyst--The preparation of polyurethane elastomer sheet is as follows:

[0172] Step 1: Weigh 90 parts of polytetrahydrofuran diol by weight, dehydrate at 130°C for 1h under vacuum conditions, cool to 80°C, add 50 parts of 2,4-toluene diisocyanate and mix well, react at 120°C for 50min to obtain a prepolymer. Then, preheat 10 parts of chain extender MOCA at 120°C, add to the prepolymer and stir, react at 120°C under vacuum conditions for 20min, and complete the preliminary preparation before injection molding.

[0173] Step 2: In Figure 1 The bottom of the mold with a specific shape (including water holes, area 200cm 2 ) is spread with a layer of mixed powder (including activated carbon powder, metal powder (cobalt) and sodium chloride powder), the mold is preheated to 110°C, and then the rubber compound prepared in step 1 is poured into the mold, and a layer of the above-mentioned mixed powder is quickly sprinkled on the surface (including 0.8g of activated carbon powder, 1.4g of metal powder and 1.4g of sodium chloride powder on the surface of the mold), and the rubber compound is waited for proper gelation, the mold is closed and the pressure is increased to obtain an initial sheet material, with catalyst powder attached to both the upper and lower surfaces of the sheet material.

[0174] Step 3: Add 10 parts of sulfur, 5 parts of vulcanization accelerator (dibenzothiazole disulfide), 40 parts of reinforcing agent (carbon black N220), and 70 parts of flake material, and perform programmed vulcanization on the initial flake material obtained in the third step, vulcanize it at a low temperature of 80°C for 10 minutes, vulcanize the powdered metal catalyst on the surface to form sulfide metal, and then vulcanize it at a high temperature of 140°C for 10 minutes to vulcanize the initially prepared polyurethane elastomer flake.

[0175] Step 4: After the vulcanized sheet material is cooled, it is soaked in water to dissolve the sodium chloride on the surface, increase the roughness of the surface of the sheet, and then dried to obtain the finished polyurethane elastomer sheet, i.e. Figure 2 Catalyst shown.

[0176] Fig. 9 This is a scanning electron microscope image of the catalyst prepared in this example. It can be clearly seen from the image that metal particles of cobalt (Co) are successfully embedded on the surface of the catalyst;

[0177] Fig.10 This is an EDS image of the catalyst surface prepared in Example 1 of the present invention. It can be seen from the figure that carbon (C) is evenly distributed on the catalyst surface, which comes from the powdered activated carbon layer finally loaded on the catalyst surface;

[0178] Fig.11 This is an EDS image of the catalyst surface prepared in Example 1 of the present invention. It can be seen from the image that cobalt (Co) is embedded in the catalyst.

[0179] Fig.12 The EDS image of the catalyst surface prepared in Example 1 of the present invention is Fig.11 Correspondingly, it can be seen from the figure that the distribution of oxygen (O) and cobalt (Co) has a great overlap.

[0180] 2-2) Preparation of catalyst system (catalytic capsule):

[0181] Step 5: Cut the polyurethane elastomer sheet obtained in step 4 into small sheets of 6.5 cm × 0.7 cm in length and width, such as Figure 3 As shown, it can be arched into the outer plastic cage.

[0182] Step 6: Put the three small slices made in step 5 into the square plastic cage (length, width and height 3cm×3cm×3cm) with water holes on the surface of each collection in an arched shape, and close the top cover to make a single Fig.13 The catalytic capsules shown are prepared in batches using the same method.

[0183] Example 2

[0184] Ozone catalytic oxidation verification experiment

[0185] Step 7: The catalytic capsules prepared in Example 1 were used to carry out an ozone catalytic oxidation experiment. Pyrazole was used as the target pollutant. A certain number of catalytic capsules were placed in a columnar reactor containing a pyrazole solution. Figure 5As shown, the catalyst filling volume accounts for 50% of the reactor filling area, ozone and oxygen of specified concentrations are aerated through the bottom of the reactor, and the catalytic capsules are filled with the entire reactor by air flow and water flow. The reaction time is set to 60 minutes to examine the performance of the catalyst in catalytic ozone oxidation of organic matter.

[0186] The pyrazole concentration is 100 mg / l, the total volume of the water to be treated is 500 ml, the catalyst prepared in Example 1 of the present invention is added at a concentration of 0.828 g / 100 ml, the ozone concentration is 5 mg / L, and the flow rate is 0.5 L / min.

[0187] Comparative Example 1

[0188] The catalyst used in this comparative example is the same as the catalyst prepared in Example 1, the only difference being that:

[0189] The "polyurethane elastomer sheet (a small sheet of 6.5 cm × 0.7 cm in length and width)" obtained by the treatment in step 5 was directly put into the reactor to carry out the ozone catalytic oxidation verification experiment, and was no longer prepared in the form of capsules (the total number of sheets used was the same as the number of sheets inside all the capsules used in Example 1); the remaining ozone catalytic oxidation verification experimental conditions of this comparative example were the same as those in Example 2.

[0190] A control experiment was carried out using the catalytic capsule catalyst prepared in Example 1 and the single polyurethane elastomer flake catalyst prepared in Comparative Example 1 (not combined into a catalytic capsule form), a continuous flow ozone catalytic oxidation degradation experiment was carried out and compared with a single ozone oxidation degradation experiment, and the target pollutant was pyrazole.

[0191] from Figure 6 It can be seen that the polyurethane elastomer sheet catalytic capsule prepared by Example 1 of the present invention has a better removal effect on pyrazole than a single polyurethane elastomer sheet catalyst within 60 minutes and under the same reaction conditions, and the removal effect of pyrazole by two forms of polyurethane elastomer sheet catalyst is better than that of single ozone oxidation degradation. In general, the catalytic capsule made based on polyurethane elastomer sheet has good catalytic ozone performance, saves a large number of internal invalid structures of traditional granular catalysts, and has a light weight and good mass transfer.

[0192] Comparative Example 2

[0193] The catalytic capsules used in this comparative example are the same as those in Example 1. The ozone catalytic oxidation verification experiment in this comparative example is basically the same as that in Example 2, with the only difference being the change in the amount of catalyst in the catalytic capsule and the filling ratio of the catalyst. In this comparative example, the filling volume in the catalytic capsule accounts for 100% of the filling area of ​​the reactor (i.e., the added concentration of the catalyst prepared in Example 1 of the present invention is 1.656 g / 100 ml), and the rest is the same as that in Example 2.

[0194] A comparative experiment was carried out with Example 2 and Comparative Example 2. Figure 7 It can be seen that the removal effect of target pollutants when the catalytic capsule filling volume accounts for 50% of the reactor filling area is better than when the catalyst filling volume accounts for 100% of the reactor filling area. For the same type of catalyst material, when the reactor is not filled, it is more conducive to its movement in the reactor and the mass transfer effect is better. Therefore, selecting an appropriate amount of catalyst is also conducive to improving catalytic efficiency.

[0195] Example 3

[0196] Validation experiment of cyclic ozone catalytic oxidation

[0197] Under the same conditions as in Example 2 above, a cyclic ozone catalytic oxidation experiment was carried out on the same batch of catalytic capsules. Figure 8 As shown, the catalyst prepared in Example 1 of the present invention, when recycled 5 times in a circular ozone catalytic oxidation verification experiment, has a total loss rate of less than 10%wt of the recovered catalyst.

[0198] Example 4

[0199] 1-1) Catalyst - Polyurethane Elastomer Sheet:

[0200] This embodiment provides a catalyst, the catalyst comprising a substrate with a thickness H1 of 600 μm, and component I and component II located on the substrate are powders with adsorptivity;

[0201] The substrate is made of polyurethane elastomer, and has pores on its upper and lower surfaces formed by the dissolution of the pore-forming agent. The substrate also has channels that penetrate its thickness.

[0202] The component I is cobalt and iron metal (metal sulfide / metal oxide); calculated by weight percentage, the amount of the metal accounts for 25wt% of the total amount of the catalyst; the elastomer includes a vulcanized elastomer, and the metal combines with sulfur in the elastomer to form a metal sulfide.

[0203] The component II is an activated carbon powder with a particle size of 40 to 60 μm;

[0204] 2-1) Catalyst system (hereinafter also referred to as catalytic capsule):

[0205] A polyurethane elastomer sheet of 20 cm × 10 cm in length and width is cut into small sheets, which in this embodiment are 6.5 cm × 0.7 cm in length and width, and stuffed into each collected square plastic cage (length, width and height 3 cm × 3 cm × 3 cm) with water holes on the surface to make a single catalytic capsule that can be stuffed into the external plastic cage in an arched shape.

[0206] 1-2) Catalyst--The preparation of polyurethane elastomer sheet is as follows:

[0207] Step 1: Weigh 100 parts of polytetrahydrofuran diol by weight, dehydrate at 120°C for 1.5 hours under vacuum conditions, cool to 75°C, add 45 parts of 2,4-toluene diisocyanate and mix well, react at 130°C for 45 minutes to obtain a prepolymer. Then, preheat 20 parts of chain extender MOCA at 130°C and add to the prepolymer, stir, and react at 130°C under vacuum conditions for 20 minutes to complete the preliminary preparation before injection molding.

[0208] Step 2: In Figure 1 The bottom of the mold with a specific shape (including water holes, area 200cm 2 ) is spread with a layer of mixed powder (including activated carbon powder, metal powder (cobalt, iron) and sodium nitrate powder), the mold is preheated at 120°C, and then the rubber compound prepared in step 1 is poured into the mold, and a layer of the above-mentioned mixed powder is quickly sprinkled on the surface (including 1.0g of activated carbon powder, 1.2g of metal powder and 1.2g of sodium nitrate powder on the surface of the mold), waiting for the rubber compound to gel properly, closing the mold and increasing the pressure to obtain an initial sheet material, with catalyst powder attached to both the upper and lower surfaces of the sheet material.

[0209] Step 3: Add 8 parts of sulfur, 5 parts of vulcanization accelerator (dibenzothiazole disulfide), 50 parts of reinforcing agent (carbon black N220), and 70 parts of flake material, and perform programmed vulcanization on the initial flake material obtained in step 2, vulcanize at a low temperature of 90°C for 15 minutes, vulcanize the powdered metal catalyst on the surface to form sulfide metal, and then vulcanize at a high temperature of 160°C for 15 minutes to vulcanize the initially prepared polyurethane elastomer flake.

[0210] Step 4: After the vulcanized sheet material is cooled, it is soaked in water to dissolve the sodium nitrate on the surface, increase the roughness of the surface of the sheet, and then dried to obtain the finished polyurethane elastomer sheet, i.e. Figure 2 Catalyst shown.

[0211] 2-2) Preparation of catalyst system (catalytic capsule):

[0212] Step 5: Cut the polyurethane elastomer sheet obtained in step 4 into small sheets of 6.5 cm × 0.7 cm in length and width, such as Figure 3 As shown, it can be arched into the outer plastic cage.

[0213] Step 6: Put the three small slices prepared in step 5 into each collected square plastic cage (3cm×3cm×3cm) with water holes on the surface in an arched shape, close the top cover to form a single catalytic capsule, and batch produce catalytic capsules using the same method.

[0214] Example 5

[0215] 1-1) Catalyst - Polyurethane Elastomer Sheet:

[0216] This embodiment provides a catalyst, the catalyst comprising a substrate with a thickness H1 of 800 μm, and components I and II on the substrate which are adsorbent powders;

[0217] The substrate is made of polyurethane elastomer, and has pores on its upper and lower surfaces formed by the dissolution of the pore-forming agent. The substrate also has channels that penetrate its thickness.

[0218] The component I is cobalt and copper metal (metal sulfide / metal oxide); calculated by weight percentage, the amount of the metal accounts for 15wt% of the total amount of the catalyst; the elastomer includes a vulcanized elastomer, and the metal combines with sulfur in the elastomer to form a metal sulfide.

[0219] The component II is an activated carbon powder with a particle size of 40 to 60 μm;

[0220] 2-1) Catalyst system (hereinafter also referred to as catalytic capsule):

[0221] A 20cm×10cm long and wide polyurethane elastomer sheet was cut into small sheets and stuffed into each collected square plastic cage (3cm×3cm×3cm) with water holes on the surface to make a single catalytic capsule that could be stuffed into the outer plastic cage in an arched shape.

[0222] 1-2) Catalyst--The preparation of polyurethane elastomer sheet is as follows:

[0223] Step 1: Weigh 80 parts of polytetrahydrofuran diol by weight, dehydrate at 140°C for 2h under vacuum conditions, cool to 85°C, add 40 parts of 2,4-toluene diisocyanate and mix well, react at 140°C for 60min to obtain a prepolymer. Then, preheat 15 parts of chain extender MOCA at 120°C, add to the prepolymer and stir, react at 120°C under vacuum conditions for 20min, and complete the preliminary preparation before injection molding.

[0224] Step 2: In Figure 1 The bottom of the mold with a specific shape (including water holes, area 200cm 2) is spread with a layer of mixed powder (including activated carbon powder, metal powder (cobalt, copper mixed powder) and potassium nitrate powder), the mold is preheated to 110°C, and then the rubber compound prepared in step 1 is poured into the mold, and a layer of the above-mentioned mixed powder is quickly sprinkled on the surface (including 0.6g of activated carbon powder, 1.6g of metal powder and 1.4g of potassium nitrate powder on the surface of the mold), wait for the rubber compound to gel properly, close the mold and increase the pressure to obtain an initial thin sheet material, with catalyst powder attached to both the upper and lower surfaces of the thin sheet material.

[0225] Step 3: Add 10 parts of sulfur, 5 parts of vulcanization accelerator (dibenzothiazole disulfide), 45 parts of reinforcing agent (carbon black N220), and 70 parts of flake material, and perform programmed vulcanization on the initial flake material obtained in step 2, vulcanize at a low temperature of 85°C for 10 minutes, vulcanize the powdered metal catalyst on the surface to form sulfide metal, and then vulcanize at a high temperature of 150°C for 10 minutes to vulcanize the initially prepared polyurethane elastomer flake.

[0226] Step 4: After the vulcanized sheet material is cooled, it is soaked in water to dissolve the potassium nitrate on the surface, increase the roughness of the surface of the sheet, and then dried to obtain the finished polyurethane elastomer sheet, i.e. Figure 2 Catalyst shown.

[0227] 2-2) Preparation of catalyst system (catalytic capsule):

[0228] Step 5: Cut the polyurethane elastomer sheet obtained in step 4 into small sheets of 6.5 cm × 0.7 cm in length and width, such as Figure 3 As shown, it can be arched into the outer plastic cage.

[0229] Step 6: Put the three small slices prepared in step 5 into each collected square plastic cage (3cm×3cm×3cm) with water holes on the surface in an arched shape, close the top cover to form a single catalytic capsule, and batch produce catalytic capsules using the same method.

[0230] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described with reference to the preferred embodiments of the present invention, it should be understood by those skilled in the art that various changes may be made in form and details without departing from the spirit and scope of the present invention as defined in the appended claims.

Claims

1. A catalyst, characterized in that The catalyst comprises a substrate, and a component I located on the substrate; The matrix includes a polyurethane elastomer; The component I has catalytic activity, and the component I includes one or more metals, and the metals include any one or two or more of iron, cobalt, nickel, copper, zinc, and titanium; Calculated by weight percentage, the amount of the metal accounts for 15-25wt% of the total amount of the catalyst; in, The metal comprises a metal sulfide which has been sulfided; or, The elastomer comprises a vulcanized elastomer; or, The metal comprises a metal sulfide that has been vulcanized, and the elastomer comprises an elastomer that has been vulcanized; or The elastomer includes an elastomer that has been vulcanized, and the metal combines with sulfur in the elastomer to form a metal sulfide.

2. The catalyst according to claim 1, characterized in that The catalyst further comprises a component II located on a substrate; the component II is a powder having adsorptivity; and / or, The surface of the substrate has pores formed after the pore-forming agent is dissolved.

3. The catalyst according to any one of claims 1 to 2, characterized in that The substrate is a layered substrate, and a channel penetrating the thickness of the layered substrate is provided; and / or, The thickness H1 of the layered substrate is 200-800 μm.

4. A catalytic system comprising a catalyst, characterized in that The catalytic system comprises the catalyst according to any one of claims 1 to 3, and a system component that causes the catalyst to deform; The component is preferably a porous shell or a porous membrane.

5. A method for preparing a catalyst, characterized in that: The following steps are involved: (A) preparing a liquid matrix containing polyurethane, or a raw material liquid for synthesizing a matrix containing polyurethane; Prepare the mold; preparing a powder raw material, wherein the powder raw material includes a metal component; (B) laying the powder raw material on the surface of the mold; (C) injecting the liquid matrix or raw material liquid into a mold; Spreading powdered raw materials on the surface of the liquid matrix or raw material liquid in the mold; (D) curing treatment; (E) The product obtained by the curing treatment is subjected to a vulcanization treatment using a vulcanizing composition.

6. The method for preparing the catalyst according to claim 5, characterized in that: The powdered raw material further comprises a component having adsorption properties; and / or, The powder raw material further comprises a porogen component, which is preferably water-soluble; and / or, The bottom of the mold is provided with a plurality of protrusions; the protrusions are used to form channels penetrating the thickness of the catalyst in the thickness direction.

7. The method for preparing a catalyst according to claim 6, characterized in that: The method further comprises the step (F): performing a decomposition treatment of the pore-forming agent.

8. The method for preparing a catalyst according to any one of claims 5 to 7, characterized in that: The metal includes any one or two or more of iron, cobalt, nickel, copper, zinc and titanium, and the amount of the metal on the mold surface is 0.006-0.008 g / cm 2 ; and / or, The component with adsorption performance includes any one or two or more of activated carbon, graphene, zeolite molecular sieve, activated alumina, and diatomaceous earth; and the amount of the component on the mold surface is 0.002-0.006 g / cm 2 ; and / or, The components with pore-forming ability include but are not limited to one or more of NaCl, Na2CO3, NaNO3, Na2SO4, KCl, K2CO3, K2SO4, KNO3, MgCl2, Mg(NO3)2, MgSO4, ZnCl2, CuCl2, CuSO4, CaCl2, pentaerythritol, glucose, sucrose, and lactose; and the amount of the components on the mold surface is 0.004-0.009 g / cm 2 . and / or, The vulcanization treatment in step (E) includes low temperature vulcanization and high temperature vulcanization; The temperature of the low-temperature vulcanization is no more than 90°C, and the vulcanization time is 5 to 10 minutes; preferably 70 to 80°C; The high temperature vulcanization temperature is not less than 120°C, and the vulcanization time is 5 to 10 minutes; preferably 130 to 150°C. The vulcanization composition comprises a vulcanizing agent, a vulcanization accelerator and a reinforcing agent, and the mass ratio of the three to the elastomer is (5-10): (3-5): (40-50): (70-90).

9. Use of the catalyst according to any one of claims 1 to 3, or the catalyst catalytic system according to claim 4, or the catalyst prepared by the method according to any one of claims 5 to 8, characterized in that: It is applied to catalytic oxidation for water treatment.

10. Use of the catalyst according to claim 9, characterized in that: During the application process, the catalyst is placed in a tensile, and / or compressive, and / or torsion deformation state.